Endophyte infection, nutrient status of the soil and duration of snow cover influence the performance of meadow fescue in sub-artic conditions - Wäli, P. R.; Helander, M.; Nissinen, Oiva; Lehtonen, P.; Saikkonen, K. (Grass and Forage Science, 2008)
v 2008 ok